GESTÃO AMBIENTAL EM MICRO E PEQUENOS EMPREENDIMENTOS DE BASE FAMILIAR: ENTRE O DISCURSO E A PRÁTICA GERENCIAL - Teixeira, Enise B.; Grzybovski, Denize; Fernandes, Sandra B. V.; Schiavo, Rodrigo L.; Basso, Mariana C. (Salão do Conhecimento, 2013)
Resumo